2013
DOI: 10.1088/0256-307x/30/7/077701
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-Scale Flexible Surface Acoustic Wave Devices Based on an AlN/Si Structure

Abstract: Wafer-scale flexible surface acoustic wave (SAW) devices based on AlN/silicon structure are demonstrated. The final fabricated devices with a 50𝜇m-thickness silicon wafer exhibit good flexibility with a bending curvature radius of 8 mm. Measurements under free and bending conditions are carried out, showing that the central frequency shifts little as the curvature changes. SAW devices with central frequency about 191.9 MHz and 𝑄-factor up to 600 are obtained. The flexible technology proposed is directly appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Fig. 2(b) is the simulated reflection spectrum using the COMSOL Multiphysics for FBAR on PET substrate with the actual device parameters and material properties [2][3][4]. Although the actual device has poor reflection than the simulated one, both have the same resonant frequencies, indicating the peak is indeed the resonant wave in the FBARs on PET.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 2(b) is the simulated reflection spectrum using the COMSOL Multiphysics for FBAR on PET substrate with the actual device parameters and material properties [2][3][4]. Although the actual device has poor reflection than the simulated one, both have the same resonant frequencies, indicating the peak is indeed the resonant wave in the FBARs on PET.…”
Section: Resultsmentioning
confidence: 99%
“…A virtual ambience was created to motivate children during pediatric motor rehabilitation, by means of a system based on RFSs for measuring thumb, index and middle finger movements, converted into virtual object manipulations on a screen [102]. Similarly, a low-cost viable hand rehabilitation system was developed within an augmented reality system [13], and a rehabilitation game supported the upper extremity movements recorded by means of RFSs [194].…”
Section: Virtual/augmented Environmentmentioning
confidence: 99%
“…Alternatives are provided by electrogoniometers, which still suffer crosstalk problems [9], and electromagnetic motion capturing systems, such as the ones produced by Polhemus or Ascension [10], whose correct usage requires an electromagnetic free environment. Other possibilities are represented by elastic sensors [11], surface acoustic wave (SAW) sensors [12,13], and polymeric stretchy capacitors (by Stretchsense, Onehunga, Auckland), but without meaningful support from the literature since their full properties are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In flex sensors, also known as flexion or flection sensors, as the bending of material attached to it changes the resistance of the circuit changes accordingly (Saggio et al, 2016). Saggio et al (2016) also reported that measurement of flexion can be achieved by means of various sensors such as fiber Bragg grating sensors (Al-Fakih et al, 2012), accelerometers (Luinge et al, 2007) gyroscopes (Williamson and Andrews, 2001), magnetometers (Bonnet and Héliot, 2007), elastic sensors (Saggio et al, 2014), surface acoustic wave (SAW) sensors (Preethichandra and Kaneto, 2007;Zhang et al, 2013), and optical coordinate capturing systems (Beth et al, 2003) etc. However, recent developments in flex sensor technologies enable designers to improve measurement sensibility and related accuracy.…”
Section: Introductionmentioning
confidence: 99%